Connecting the Dots: Multivariate Analysis of the Link between Lecture Attendance, Reading Time, and Student Success - Otunomeruke, James Allen; Omosioni, P. E. (Advances in Social Sciences Research Journal, 2025)
This study, "Connecting the Dots: Multivariate Analysis on the links between lecture attendance, reading time, resource materials utilization and student success," investigates the interplay between critical academic factors and their combined impact on tertiary students’ performance. A cross-sectional survey was conducted using probability sampling techniques in picking four out of six faculties in the Southern Delta University, Ozoro, Nigeria. Four hundred students were chosen into the study from 200 and 300 levels, and structured questionnaire was employed in data collection on personal interviews. Multivariate analysis was carried out using SPSS (version 26) to examine the relationship and connectivity between lecture attendance, reading time, reference material utilization, and grade point average respectively. Findings indicate strong positive correlation (R = 0.728, p<0.05) between lecture attendance and academic performance. While a higher correlation (R-value of 0.748, p=0.000) among students who regularly attend lectures and success was observed. Findings also show a positive relationship between frequency of lectures’ attendance and academic performance (R=.601, p-value =0.000), indicating this variable is statistically significant. Similarly, students who dedicated more hours to reading outside of classroom show better academic outcomes (R-value of 0.355, p=0.000), and those with less hours in reading recorded lower success (R = 0.315, p=0.000) level. Equally, the study noted an optimal range of 2-3 hours of self-study among the students. Hence, individual student should identify his/her optimal study hours capability and adhere to it for maximum comprehension, assimilation and retention. Stakeholders in educational sector should provide solutions to factors causing absenteeism in the class.